2017
DOI: 10.1177/2167696817739022
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Racial Discrimination That Predict Problematic Alcohol Use Among African American Emerging Adults

Abstract: The association between racial discrimination (discrimination) and problematic alcohol use in African American (AA) emerging adults is well-documented. Few researchers, however, have studied the longitudinal relationship between discrimination and problematic alcohol use among AA male and female emerging adults. In a sample of 681 AAs aged 19-25 (51% male), we explored multiple, distinct trajectories of discrimination and sociodemographic predictors of the trajectory classifications. We also examined the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…Our study is not the first to document gender variations in the consequences of PRD. Researchers have found that the effects of PRD on several undesired mental health outcomes from psychological distress and depression to suicide and substance use differ by sex (31, 35, 36, 38). In addition to gender, socioeconomic status (23, 57, 58), racial identity (59), race socialization and self-esteem (60) also alter sensitivity to PRD, which is more commonly reported by high SES Blacks, particularly males who are in proximity of Whites (6163).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is not the first to document gender variations in the consequences of PRD. Researchers have found that the effects of PRD on several undesired mental health outcomes from psychological distress and depression to suicide and substance use differ by sex (31, 35, 36, 38). In addition to gender, socioeconomic status (23, 57, 58), racial identity (59), race socialization and self-esteem (60) also alter sensitivity to PRD, which is more commonly reported by high SES Blacks, particularly males who are in proximity of Whites (6163).…”
Section: Discussionmentioning
confidence: 99%
“…The harmful effects of PRD, however, may vary by gender, with males being more vulnerable than females to the effects of PRD on depression and substance use (26, 31, 3538) and females being more sensitive to the effects of PRD on other health behaviors, such as obesity and eating disorders (39). Some scholars have documented gender differences in experience and response to discriminatory events.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, research on perceived discrimination trajectories and mental health was concentrated mainly among adolescents and emerging adults ( 30 , 40–42 ), with limited studies among middle-aged and older adults ( 43 , 44 ). In a study of African American early adults (aged 18–21), three perceived discrimination trajectories (i.e., high-stable, low-increasing, and low-decreasing) were identified ( 41 ). African American men in the high-stable perceived discrimination trajectory reported more alcohol use than men in other trajectories ( 41 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…In a study of African American early adults (aged 18–21), three perceived discrimination trajectories (i.e., high-stable, low-increasing, and low-decreasing) were identified ( 41 ). African American men in the high-stable perceived discrimination trajectory reported more alcohol use than men in other trajectories ( 41 ). More importantly, findings from these studies have shown that membership in perceived discrimination trajectories is associated with unique health profiles ( 30 , 40–42 ).…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Several researchers have reported on the negative effect of RD on intermediate health behaviors in older adolescents and emerging adults, including alcohol use (Metzger et al, 2018) and its related problems (e.g., physical consequences of excessive alcohol use; D. B. Lee et al, 2018).…”
Section: Racial Discrimination and Alcohol-related Problemsmentioning
confidence: 99%